Description of Nutritional Knowledge of Mothers Who Give Birth to Low Birth Weight Babies and Non-Low Birth Weight Babies at Tidar Hospital, Magelang - Chomsatun, Chomsatun; Sulistiani, Ria Purnawian; Handasari, Erma; Jauharany, Firdananda Fikry; Fauziah, Wardah; Marianthi, Dewi (Journal Keperawatan, 2024)
Background: The impact of babies with the Low Birth Weight (LBW) category in the long term can have a risk of experiencing respiratory disorders, infections, and even death. The incidence of LBW can be influenced by gestational age of less than 37 weeks, maternal age of less than 20 years or more than 35 years, pregnancy spacing, maternal occupation, and maternal nutritional knowledge. Purpose:  Describe the nutritional knowledge of mothers who give birth to LBW and non-LBW babies at Tidar Hospital Magelang Methods: This type of research is descriptive with a Cross Sectional research design. The study population was mothers who gave birth in April 2022 at Tidar Hospital, Magelang. The sampling method was carried out using the total sampling technique with a total of 20 respondents. Primary data collection techniques include filling out questionnaires and interviewing respondents directly. Results: The number of mothers who are included in the category of having LBW babies is 3 people (15%) and mothers with the category of Non-LBW Babies are 17 people (85%). The nutritional knowledge of mothers with the category of LBW babies has a good, sufficient, and less score which is evenly distributed, namely 1 respondent each. While those who are Non-LBW have a good score of 13 respondents, a sufficient score of 1 respondent, and a less score of 3 respondents. Conclusion: Mothers who give birth to babies in the non-LBW category have better nutritional knowledge than mothers who give birth to babies in the LBW category.